2012
DOI: 10.1152/ajpgi.00457.2011
|View full text |Cite
|
Sign up to set email alerts
|

Dietary 1-monoolein decreases postprandial GIP release by reducing jejunal transport of glucose and fatty acid in rodents

Abstract: -Postprandial secretion of insulin and glucose-dependent insulinotropic polypeptide (GIP) is differentially regulated by not only dietary carbohydrate but also fat. Recent studies have shown that the ingestion of diacylglycerol (DAG) results in lower postprandial insulin and GIP release than that of triacylglycerol (TAG), suggesting a possible mechanism for the antiobesity effect of DAG. The structural and metabolic characteristics of DAG are believed to be responsible for its beneficial effects. This study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…The ablation of GIP-secreting K cells enhanced energy expenditure and reduced HF diet-in- duced obesity in mice (3). Our recent study showed that RS4-type resistant starches and 1-monoolein reduced postprandial GIP and insulin responses, resulting in an increase in fat utilization and reduced HF diet-induced obesity in mice (36,37). The present results are consistent with the findings of previous studies and suggest that the reduction in postprandial blood GIP levels by TASP enhanced fat utilization, thereby preventing HF diet-induced obesity.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The ablation of GIP-secreting K cells enhanced energy expenditure and reduced HF diet-in- duced obesity in mice (3). Our recent study showed that RS4-type resistant starches and 1-monoolein reduced postprandial GIP and insulin responses, resulting in an increase in fat utilization and reduced HF diet-induced obesity in mice (36,37). The present results are consistent with the findings of previous studies and suggest that the reduction in postprandial blood GIP levels by TASP enhanced fat utilization, thereby preventing HF diet-induced obesity.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, we previously demonstrated that the increase in blood GIP levels induced by the chronic administration of GIP decreased fat utilization in high-fat diet-fed mice (37). Our previous studies also revealed that the administration of dietary components that lowered postprandial blood GIP levels, such as diacylglycerol (35), 1-monoolein (36), and RS4-type resistant starch (37) increased fat catabolism and prevented high-fat diet-induced obesity in mice. Postprandial fat utilization was higher with the intake of either diacylglycerol (35) or RS4 (37) than with its equivalent control oil or carbohydrate in humans.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…On the other hand, the use of MG as a regulator in postprandial insulin level has been patented (Takeno, Shimotoyodome, & Meguro, 2009). Recently, Shimotoyodome et al (2012) reported that dietary 1-monoolein stimulated fat utilization, and attenuated induced obesity, postprandial lipemia and insulin response in mice.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, intravenous administration of GIP to healthy lean men lowers resting energy expenditure (REE) [26]. In our previous study, we found that the dietary components that control GIP secretion, such as diacylglycerol [27], 1-monoolein [28], and RS4-type-resistant starch [29], increase postprandial fat utilization and prevent high-fat diet-induced obesity in mice. Reduction of postprandial GIP secretion can increase postprandial energy catabolism and prevent obesity.…”
Section: Introductionmentioning
confidence: 99%